Test Results of Fine Sediment Fractions from the Tell el-Farkha Archaeological Site, Nile Delta, Egypt (Studies in Ancient Art and Civilisation, 2015)
The Tell el-Farkha site is located immediately to the north of the modern village of Ghazalah and occupies an area of c. 4.5ha. It is marked by three hills: the Eastern Kom, Central Kom and Western Kom. This research will focus on the profile of the layers of sediment. These studies are important because they are innovative and contain information on the history of the site. Research work was conducted on site and produced graphs showing the composition of individual microartefacts within the sediment. Samples were taken from each profile layer then dissolved and sifted to obtain fine fractions. Laboratory work focused on the calculation of the percentage of different microartefacts in each sifted fine fraction. Photographs of selected microartefacts (bones, ceramics, carbon, quartz, and others) were taken using a binocular magnifier at 20x magnification. The examination of this material has provided both new and valuable information concerning the functioning and development of the archaeo-logical site.